ORAL POTENTIALLY MALIGNANT DISORDERS ASSOCIATED WITH BETEL QUID CHEWING HABIT IN SAMOSIR ISLAND, NORTH SUMATRA INDONESIA: KELAINAN MUKOSA MULUT BERPOTENSI MALIGNA YANG DIHUBUNGKAN DENGAN KEBIASAAN MENYIRIH DI PULAU SAMOSIR, SUMATERA UTARA INDONESIA - Lubis, Indri; Primasari, Ameta; Hasibuan, Sayuti (TALENTA, 2017)
Oral potentially malignant disorders have been associated with a betel quid chewing habit. To date, betel quid chewing has a major social and cultural role in the society of Samosir Island, North Sumatra, Indonesia. The purpose of the present study was to evaluate the occurrence of oral potentially malignant disorders associated with the habit of betel quid chewing in the society of Samosir Island, North Sumatra, Indonesia. This case-control study was conducted on all betel quid chewers in the working area of the Ambarita Public Health Centre in Samosir Regency, North Sumatra, Indonesia. All subjects were examined clinically for the presence of any oral lesions and interviewed for their betel quid chewing habit. Chi-square and Fisher’s exact tests were used to analyze the relationship between variables. Among the 51 subjects recruited in the study, 28 subjects suffered from oral potentially malignant disorders who had oral potentially malignant disorders such as submucous fibrosis and/or leukoplakia (the case group) whereas 23 subjects showed no clinically detectable oral potentially malignant disorders (the control group). An increased risk of oral potentially malignant disorders was associated with the habit of chewing areca nut and tobacco (OR=1.600; p=0.542), the duration of betel quid chewing more than 25 years (OR=4.379; p=0.023), and the frequency of betel quid chewing more than 6 times/day (OR=4.800; p=0.021). In conclusion, oral potentially malignant disorders were associated with chewing betel quid habit in the society of Samosir Island, North Sumatra, Indonesia.